Climatic and Economic Factors Affecting the Annual Supply of Wild Edible Mushrooms and Berries in Finland - Veera Tahvanainen; Jari Miina; Mikko Kurttila (Forests, 2019)
Finnish non-timber forest products (NTFPs) are valued on the national and international markets. Yet, the annual marketed quantities vary considerably, causing instability in supply chains. Thus, climatic and economic factors affecting the annually aggregated supply of top-marketed mushrooms (ceps, milk caps, and chanterelle) and berries (bilberry, cowberry, and cloudberry) in Finland were studied. Data on mushroom and berry market prices (€/kg) and quantities (kg) were obtained from the statistics on annual quantities of berries and mushrooms bought by organized trade and industry in Finland (1978–2016). The species-specific supply functions were described as linear regression models, where annually aggregated quantities were predicted as a function of climatic and economic variables. Our results suggested that climatic variables influenced the marketed quantities of NTFPs through the biological yields of berries and mushrooms, and that the market price had a negative effect on the marketed quantities of ceps, milk caps, and berries. The markets for NTFPs have become more international at the second half of the study period (1999–2016), modifying the price-quantity relationships of ceps, milk caps and cloudberries. Additionally, the number of visas issued to Thai pickers increased the marketed quantities of bilberries and cowberries.